Heap Leaching Practice At The Carlin Gold Mining Co. , Carlin, Nev. - Ramon Pizarro; J. D. McBeth; G. M. Potter (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
Heap leaching is used by the Carlin Gold Mining Co., Carlin, Nev., to supplement conventional processing of gold ore by agitation-leaching and countercurrent decantation. Selected open-pit ore containing about 0.072 oz Au per ton is crushed to 3/4 inch, dumped by truck on an asphalt pad, and leached by sprinkling with dilute cyanide solution for 7 days. The heap is then drained and removed by front-end loader to tailings disposal. About 70 percent of the gold is dissolved. Leach solution from the heap joins the pregnant solution from countercurrent decantation for gold recovery by zinc precipitation. Four leach pads, each with a capacity of 1,400 tons of ore, are in use. About 10,000 tons of ore are heap leached monthly from about April through October. Heap leaching is recessed during freezing weather. Labor, equipment, and reagent requirements for heap leaching are presented.